Design of government agency’s performance accountability system best practice implementation: Indonesia experience - Panggalih, Fatih Henggar; Bastian, Indra (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to explain the performance accountability system best practice implementation of Yogyakarta Special Region’s (Yogyakarta) Local Government through a valid and reliable design that is ready to be adopted and used as a role model by other local governments.Design/Methodology/Approach: This research used a qualitative method with a case study approach to reach the research objective. Research data was collected using in-depth interviews and documentation techniques.Research findings: This study succeeds in realizing a design by providing an applicable template as a recommendation tool compiled from seventeen items of success measures that are the performance accountability system’s best practices at the Yogyakarta Local Government. This study becomes more complex because it has been equipped with simulations of template filling out as well as a comparative analysis of the performance accountability system’s implementation between the Yogyakarta Local Government and the Central Java Local Government. The results of filling out the template for the Central Java Local Government revealed that 88% of the success measures have been applied, and another 12% have not.Theoretical contribution/Originality: This study provides an academic contribution as a reference related to the performance accountability system of government agencies.Practitioner/Policy implication: This study also provides a practical contribution to other local governments regarding the application of the performance accountability system’s best practices at the Yogyakarta Local Government through the design of the performance accountability system’s best practices that can be adopted and used as a role model in strengthening the performance accountability system.Research limitation/Implication: This study has limitations, namely that the researcher was unable to conduct interviews with the Ministry of Administrative and Bureaucratic Reform due to communication problems, which prevented the interview process from being carried out.